ANALISIS BREAK EVENT POINT (BEP) MULTY PRODUCT UNTUK PERENCANAAN LABA DENGAN PENDEKATAN LINIER PROGRAMMING METODE SIMPLEK - Titop Dwiwinarno; Ferri Kuswantoro (MANAJEMEN, 2024)
The purpose of this study is to determine the level of break event point multi product and the amount of sales to achieve the planned profit level using linear programming simplex method. From secondary data provided by CV MD Company located in Bantul D.I Yogyakarta. The results of the study indicated that to achieve the break event point multi product the amount of demand was for product X5 (stool copis M product) with a contribution margin value of Rp. 168,500,000.00. The amount of demand if the company planed  a profit of Rp. 20,000,000.00 then the level of demand for product X5 was 1,448 units.